Pemahaman Pengguna Media Sosial Tinder terhadap Fenomena Kencan Online untuk Menjalin Hubungan Romantis Bagi Penggunanya - Kinasih Dwi Cessia; Sri Budi Lestari (Interaksi Online, 2018)
Online Dating is a social phenomenon that is being popular among people active online users. Supported by an advance technology such as the internet and gadgets, online dating activities may generate new connections even in a romantic relationship. Online dating activities have different understandings for each user. Main differences of users understanding was led the research to conduct. This research aimed to determine the diversity of understanding of social media users Tinder in a romantic relationship through online dating, and how this understanding is raised by users. The results of this study found that each informant has the comprehension distinction in understanding online dating and romantic relationships generated through online dating. There are differences in understanding the variety of comprehension with the dimension of love based on Triangular Theory of Love. First and fourth informants understand the romantic relationship through online dating as a positive and efficient. They also understand it as a deep and meaningful, even feel the relationship result through online dating relationship equal to that generated directly (non-online). So they constructed the understanding by looking for a soul mate through Tinder to dispel loneliness with a serious romantic relationship, i.e. dating. They pay attention to all of love dimension, passion, intimacy and commitment, in understanding each process relationships resulting from online dating through the Tinder. In contrast, the second and third informants understand the romantic relationship through Tinder as the casual relationship. So they constructed a limited meaning as entertainment for having a sex partner or just entertain them when they have conflict with their partner. They only pay attention to the dimensions of the passion in understanding romantic relationships that result from online dating through Tinder.